The influence of quality of opposition on covered distance during soccer match - Alvarez-Pastor, D.; Casamichana, D.; Castellano, J. (7th World Congress on Science and Football (WCSF), 2011, 2011)
The aim of this study was to determine the physical performance in professional football with the level of opposition by the rival with respect to itself, taking into account the different phases of the game (offensive and defensive phase). Methods A multi-camera computerised tracking system (AMISCO Pro®, version 1.0.2., Nice, France) was used to gather the data of 754 players in Spanish Premier League. It has distributed the level of the teams in three categories: (T1) the teams that finished the league in the top six, (T2) those finished between 7th and 13th, and (T3) those finished in the bottom between 14th to 20th position. Results & Discussion Similar to other study [1], the results show that when the team has a level much lower than the contrary, the distance traveled during the first half in defensive phase is significantly higher. When the level is the same as the opposing team, the distance traveled during the second half is significantly lower as compared to other levels. There are significant differences between the first and second half on the distance traveled in offensive phase in situations of Weak (W), Similar (SM) and Strong (S), and without the ball in a position to SM. Conclusion The present findings would serve to broaden the body of research on physical demands in elite soccer match-play, as well as improving knowledge of specific situational variables and their possible influence as regards tactical preparation for matches.